Polyamide Chain Growth and Crosslinking: The Controlling Determinants for Properties of Thin Film Composite Membrane - Beh, J. J; E. P.; Ooi, B. S. (ASEAN Journal of Chemical Engineering, 2017)
The desired features of a polyamide thin film composite (TFC) membrane for desalination can be tailored through careful control of membrane preparation condition. This work aims to provide more comprehensive understanding on polyamide film formation chemistry in order to correlate the membrane synthesis condition with its characteristics. Three series of TFC membranes were prepared by interfacial polymerization with adjustment of m-phenylenediamine (MPD) and trimesoyl chloride (TMC) monomer concentration as well as reaction duration. The membrane structural properties were evaluated based on glucose permeation then correlated with the transport and charge behaviors of membrane determined from pure water and inorganic salt permeation. During interfacial polymerization, competition occurs between polyamide chain growth and crosslinking. It was found that higher MPD concentration promoted polyamide chain crosslinking while increasing TMC concentration favored polyamide chain growth during diffusion-limited growth stage. Meanwhile, prolonged degree of polyamide chain growth and crosslinking occurred at longer reaction duration, which eventually caused self-limiting membrane growth. The water transport was primarily controlled by polyamide film thickness, porosity and hydrophilicity while size exclusion and Donnan exclusion worked in tandem in governing the salt separation. The TFC membrane synthesized at 3 w/v% MPD concentration and 0.10 w/v% TMC concentration under 60 s reaction duration achieved the best desalination performance with pure water permeability of 0.853 L/m2·h·bar and 81.4 % NaCl rejection.